2003
DOI: 10.1080/0003942031000086644
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplemental L-Carnitine and Ascorbic Acid on Performance, Carcass Composition and Plasma L-Carnitine Concentration of Broiler Chicks Reared Under Different Temperature

Abstract: The present study was initiated to determine whether dietary supplemental L-carnitine and ascorbic acid affect growth performance, carcass yield and composition, abdominal fat and plasma L-carnitine concentration of broiler chicks reared under normal and high temperature. During the experiment, two temperature regimes were employed in two experimental rooms, which were identical but different in environmental temperature. The regimes were thermoneutral (20-22 degrees C for 24 h) or recycling hot (34-36 degrees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(23 citation statements)
references
References 18 publications
4
16
0
1
Order By: Relevance
“…This observation conformed to that of Kutlu (2001) and Sahin, et al (2003) fat of birds on 135ppm supplemental AA and the control (unsupplemented). Other studies (Fletcher and Cason, 1991;Celik andOzturkcan, 2003 andKonca et al, 2009) also confirmed that AA supplementation had no effect on abdominal fat pad yield. Table 4.…”
Section: Resultssupporting
confidence: 53%
“…This observation conformed to that of Kutlu (2001) and Sahin, et al (2003) fat of birds on 135ppm supplemental AA and the control (unsupplemented). Other studies (Fletcher and Cason, 1991;Celik andOzturkcan, 2003 andKonca et al, 2009) also confirmed that AA supplementation had no effect on abdominal fat pad yield. Table 4.…”
Section: Resultssupporting
confidence: 53%
“…Similar results were obtained by Daskirian and Teeter (2001) and Zhang et al (2010) that the carcass yield of which increased as a result of L-carnitine supplementation, but the differences were not significant. Different results were recorded by Celik and Ozturkcan (2003), Celik et al (2003) and Kidd et al (2009) who observed that supplementation of L-carnitine had no effect on carcass yield.…”
Section: Day Of Fatteningmentioning
confidence: 82%
“…These results may be due to L-carnitine may acts to decrease the total activities of glucose-6 phosphate dehydrogenize, malic dehydrogenize, iso-citrate dehydrogenize and lipoprotein lipase and total activities of carnitine palmitoyltransferase-I in breast muscles (Xu et al, 2003). Or, it accelerate lipid flux into oxidative metabolism, and consequently reduce the body lipid accumulation (Shuenn et al, 2012).These results are contrary with those obtained by Celik and Ozturkcan (2003) reported that the supplementation of L-carnitine to the broiler diet did not significantly affect the dry matter, CP, and ether extract components of breast or thigh meat. Sarica, et al, (2005) recorded that dietary Lcarnitine supplementation did not significantly affect the dry matter or moisture, CP, and ether extract contents of the total edible meat (breast plus high meat) of 35-dold Japanese quail.…”
Section: Chemical Analysis Of Breast and Thigh Muscles:-mentioning
confidence: 86%